Double Controlled Dislocated Quasi-Metric Type Spaces and Some Results - Abdullah Shoaib; Shaif S. Alshoraify; Muhammad Arshad (Journal of Mathematics)
The aim of this work is to introduce double controlled dislocated quasi-metric type spaces and to obtain fixed point results for a pair of multivalued mappings satisfying Kannan-type double controlled contraction in such spaces. An example has been built and a remark has been given which shows that how our result can be used when a corresponding new result in dislocated quasi b-metric type spaces cannot be used. Our results generalize and extend many existing results in the literature.